Sleep in the Aging Brain - Maurizio Gorgoni; Luigi De Gennaro (Brain Sciences, 2021)
We have entered an era of a steep increase in the absolute and relative number of older people. This well-come phenomenon represents a major challenge for health care. However, maturational changes in sleep associated with aging do not easily appear as main factors, even though sleep alterations in the aging process lead to many detrimental consequences. In this editorial paper, we summarize the present knowledge about the main aging-related sleep modifications and their relevance for health problems and cognitive decline. Then, we present the papers published in the Special Issue “Disturbances of Sleep Among Older People”.